2013
DOI: 10.5657/fas.2013.0211
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Motion Characteristics of a Cod-end Caused by an Attached Circular Canvas during Tank Experiments and Sea Trials

Abstract: A shaking motion could be used to improve fish escapement from a cod-end net by creating a sieving effect over the swept volume or by disturbing the optomotor response of the fish. In this study, a perpendicular shaking motion was generated in a towed cod-end net by a circular canvas attached to the end of the codend, which formed a biased cap-like shape. This concept was tested by using a model in a flow tank and by towing a prototype cod-end during sea trials. For the model tests, the amplitude of the shakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The retention rate of juvenile fish such as red seabream (Kim and Whang, 2010) or bastard halibut (Kim, 2011) the sweeping motion of the fluttering netting panel inside the codend could be limited by turbulent flow and the catch. Therefore, a new method to encourage fish to approach the netting panel of the codend has been suggested where the codend is moved up and down by forming a cap-like canvas (Kim, 2013b). The effect of vertical shaking of the codend produces a similar effect to that produced by the codend pulsing reported by O'Neill et al (2003).…”
Section: E-mail Address: Yonghae@gnukrmentioning
confidence: 90%
See 1 more Smart Citation
“…The retention rate of juvenile fish such as red seabream (Kim and Whang, 2010) or bastard halibut (Kim, 2011) the sweeping motion of the fluttering netting panel inside the codend could be limited by turbulent flow and the catch. Therefore, a new method to encourage fish to approach the netting panel of the codend has been suggested where the codend is moved up and down by forming a cap-like canvas (Kim, 2013b). The effect of vertical shaking of the codend produces a similar effect to that produced by the codend pulsing reported by O'Neill et al (2003).…”
Section: E-mail Address: Yonghae@gnukrmentioning
confidence: 90%
“…The shaking codend was generated as an oscillating motion by a cap-like round canvas using a variable lifting force. Earlier field towing experiments using a codend frame without fish have indicated that a shaking ratio of 0.5 could encourage fish to move and approach the side netting panel of the codend, which would possibly allow them to escape (Kim, 2013b). The objective of this tank test was to determine the potential for the escape of juvenile fish in a shaking codend by attaching a canvas compared with a conventional steady codend.…”
Section: E-mail Address: Yonghae@gnukrmentioning
confidence: 99%
“…The shaking motion of the cod end with a round canvas in trial S1 had a significantly greater period and amplitude than in trial S2. More than 20% of the peaks in trial S1 were of a larger amplitude (≥0.6 m, which was half of the cod end height), although the mean amplitude, 0.4 m, was one-third of the cod end height, which was smaller than the amplitude ratio in the model experiments of Kim (2013b). In addition, the mean shaking period of 14 s was longer than the period of the model cod end in the field towing experiments of Kim shaking cod end of the shrimp beam trawl was reduced by -30% compared to the steady cod end, and the shaking cod end achieved a 25% decrease in total bycatch and 24% decrease in discarded garbage.…”
Section: Resultsmentioning
confidence: 83%
“…The selectivity of juvenile fish was not affected by the size frequency, possibly due to too small a mesh size in the cod end of the shrimp trawl, although an obvious effect was observed on the reduction in weight of juvenile fish and garbage. The shaking motion generated by a round canvas can cause an unbalanced lifting force, causing cod end drag with increased towing time under turbulent flow (Kim, 2013b). Therefore, the towing velocity of the cod end on the seabed (Kim, 2012) relative to the tidal flow could also affect the period and amplitude of the shaking motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation